ANTITUMOR POTENTIAL OF HYDROETHANOLIC EXTRACT OF ANNONA MURICATA LEAVES AGAINST DALTON’S LYMPHOMA ASCITES-INDUCED TUMOR IN MICE - P, Nalini; Durairaj, Brindha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study was to assess the antitumor activity of hydroethanolic extract of Annona muricata (HEEAM) in Dalton's lymphoma ascites (DLA)-induced tumor model. Methods: Antitumor activity of HEEAM was evaluated against DLA-induced tumor mice by assessing the antitumor, hematological, and biochemical parameters. Results: The results revealed that antitumor activity of HEEAM was observed in Swiss albino mice at the doses of 200 and 400 mg/kg body weight given orally for 15 days. The results indicated that administration of the extracts not only increased the survival of animals and decreased the body weight with ascites tumor but also altered many hematological and biochemical parameters. Both extracts exhibited a significant (p<0.05) antitumor activity on dose-dependent manner. Among the two doses, 400 mg/kg of HEEAM dose showed potent anticancer activity. Conclusion: The findings confirmed that the HEEAM possess potent antitumor activity, and hence, it might be used as a natural anticancer agent